Quantification of Construction Waste through BIM - Hasan, Rakibul (Journal of Technology Management and Business, 2022)
Nowadays, green environment is a great concern in the construction industry because of its rapid growth and its direct connection with the detrimental impact on the environment. The construction sector contributes about 23% of air pollution, 50% of climatic change, 40% of drinking water pollution, and 50% of landfill waste. A developing country like Bangladesh did not use any proper waste estimation process or tools which can efficiently estimate the volume of materials needed for a construction project which always results in wasting excessive materials. Waste estimation can determine the volume of materials even in the pre-construction stage and thus reducing waste, cost and environmental impact. In light of the gap in existing tools and methods to estimate the waste amount, Building Information Modelling (BIM) based system plays a vital role to estimate construction waste in the region of the rising amount of construction waste. In this paper, the clash detection process has been described to estimate construction waste with the help of Autodesk Navisworks Manage software. The clash detection process contributes to estimating a large amount of waste among the total waste generated in a building model. Different manual approaches have also been described that can estimate the total amount of construction waste. This paper also presents an example scenario with a 4-storied residential building model to demonstrate construction waste estimation systems. The case study shows that BIM-based waste estimation using clash detection could prevent 40-45% of construction waste that might have been generated without using BIM.